Imagining ends-not-yet-in-view: The ethics of assessment as valuation in Nepali music education - Treacy, Danielle Shannon; Timonen, Vilma; Kallio, Aleksis Anja; Shah, Iman Bikram (Oxford University Press, 2019)
The intensifying diversity and fast-paced social change characterizing contemporary societies requires music education policy and practice to contend with various and at times conflicting musical and cultural values and understandings. In Nepal this situation is intensified, with a music education curriculum adopted by the Ministry of Education in 2010 guiding music teaching and learning for 77 national districts and over 125 caste/ethnic groups within a rapidly globalizing society. In this context assessment plays a key role in framing the knowledge and pedagogical approaches deemed useful or desirable for Nepali music students, and contributes to the legitimation of music as a subject and as a career. Assessment is therefore of ethical concern and warrants critical reflection if music education is to uphold democratic ideals, such as participation and equal opportunity. In this chapter we identify four institutional visions framing music education in Nepali schools. Considering these visions through John Dewey’s Theory of Valuation (LW13), we suggest that ethical deliberations regarding assessment focus on the relationships between means and ends in learning processes and thereby the quality of student experience. Leaning on Arjun Appadurai’s theories of the imagination (1996) and the capacity to aspire (2004) we then propose that imagining ends-not-yet-in-view may allow for ethical engagements with values different to one’s own and encourage reflection upon the inclusive and exclusive processes of assessment that frame whose ends-in-view count, when, how, and what for.
Keywords: assessment; capacity to aspire; ethics; institutional visions; music education